Impact of the COVID-19 Pandemic on the Management of Groin Hernia Repairs: A Nationwide Population-Based Study From the Swedish Hernia Register - Ramia Stolt, MD; Peder Rogmark, MD, PhD; Fernando Ruiz-Jasbon, MD, PhD; Johanna Österberg, MD, PhD; Kristina Ticehurst, MD, PhD; Hanna De la Croix, MD, PhD (Annals of Surgery Open)
Objective:. The aim is to assess the impact of COVID-19 pandemic on delays in elective surgeries for symptomatic groin hernias in Sweden. Background:. In Sweden, over 16,000 groin hernia repairs are performed annually, primarily in elective daycare settings. The COVID-19 pandemic led to the temporary postponement of all elective surgeries to reallocate healthcare resources and limit viral transmission. Methods:. This nationwide population-based study utilizing data from the Swedish Hernia Register compared groin hernia repairs before (2015–2019) and during (2020–2021) the pandemic. Multivariable logistic regression analysis stratified by gender was employed for the outcomes. The main outcomes were risks of emergency repair, severe complications (Clavien–Dindo ≥3b), 30-day mortality, and reoperation for recurrence. Results:. A total of 109,459 groin hernia repairs (n = 98 156 in men and n = 11 303 in women) were analyzed. The number of elective repairs declined by 22.9%, while emergency repairs only increased by 2.2% in 2020. Women had a higher risk of emergency repair during the pandemic (odds ratio: 1.38, P < 0.001) and presented notably higher crude rates of 30-day mortality and bowel resection compared with men in both cohorts. However, the overall risks in the population remained stable despite these shifts. Conclusions:. “Watchful waiting” for symptomatic groin hernias due to postponement of elective repairs in men appears safe regarding the risks of emergency repair and severe complications, in contrary to women. While elective repairs can temporally be deferred during crises, careful consideration should be given to women. Given this large-scale study, watchful waiting may not be appropriate for women in future healthcare crises, warranting further investigations.